Description of a new species and new country records of Ancognatha Erichson (Coleoptera: Scarabaeidae: Dynastinae) from Colombia - Pardo-Locarno, Luis Carlos; Gonzalez, Ranulfo; Montoya-Lerma, James (Zootaxa, 2006)
A new species, Ancognatha veliae, from the Chocó Province, Colombia is described and its morphology and taxonomic position are discussed. The species Ancognatha atacazo Kirsch, A. castanea (Erichson), and A. horrida Endrödi are recorded as new country records for Colombia.